2021
DOI: 10.2139/ssrn.3827866
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of the Median Nerve: A Systematic Review and Meta-Analysis of Normal Values in Asymptomatic Adults and How They Change in Carpal Tunnel Syndrome

Abstract: Background: Carpal tunnel syndrome (CTS) leads to distortion of axonal architecture, demyelination and brosis within the median nerve. Diffusion tensor imaging (DTI) characterises tissue microstructure and generates reproducible proxy measures of nerve 'health' which are sensitive to myelination, axon diameter, bre density and organisation. This meta-analysis summarises the normal DTI values of the median nerve, and how they change in CTS.Methods: This systematic review included studies reporting DTI of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(97 reference statements)
1
3
0
Order By: Relevance
“…Our work corroborates prior dMRI studies in peripheral nerves 16 , 17 (and the brain 56 ) which demonstrate that nerves exhibit more isotropic diffusion with advancing age. This is expected because aging axons lose their integrity, axoplasmic transport is slowed and the myelin sheath deteriorates which gives way to segmental demyelination and axonal loss without remyeliation 57 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our work corroborates prior dMRI studies in peripheral nerves 16 , 17 (and the brain 56 ) which demonstrate that nerves exhibit more isotropic diffusion with advancing age. This is expected because aging axons lose their integrity, axoplasmic transport is slowed and the myelin sheath deteriorates which gives way to segmental demyelination and axonal loss without remyeliation 57 .…”
Section: Discussionsupporting
confidence: 90%
“…Studies in the brain have shown that dMRI outputs are dependent on scanner hardware, acquisition settings, preprocessing techniques, reconstruction algorithms and extraction methods 2 , 10 – 15 . Recent work has shown similar dependence in the brachial plexus 16 and median nerve in the hand 17 . Therefore, before researchers and clinicians can reliably use dMRI to assess the ‘health’ of the major nerves of the upper limb, there is a need to define the range of “normal” values and how they vary with experimental conditions.…”
Section: Introductionmentioning
confidence: 74%
“…This study suggests that software used for preprocessing DTI improves the geometric accuracy of dMRI data from upper limb with respect to the anatomical ground truth, but this comes at the expense of introducing large differences in the diffusion metrics extracted from peripheral nerves. This is clinically important because the magnitude of variation in DTI parameters between preprocessing software is of the magnitude that might be attributable to disease or injury 52,53 . Consequently, in the absence of standardization of methods used by pipelines, readers should be aware of the potential for preprocessing to bias the output.…”
Section: Discussionmentioning
confidence: 99%
“…This is clinically important because the magnitude of variation in DTI parameters between preprocessing software is of the magnitude that might be attributable to disease or injury. 52 , 53 Consequently, in the absence of standardization of methods used by pipelines, readers should be aware of the potential for preprocessing to bias the output.…”
Section: Discussionmentioning
confidence: 99%